The Affect of Physical Parameters on Flood Potential in the Upstream River and the Musi Watershed of Kepahiang, Indonesia - Supiyati; Imania Elisa; Halauddin (Jurnal Penelitian Pendidikan IPA, 2024)
Fllod often occur if the rainfall is high, the flood-affected areas are downstream areas around the Musi Watershed of Kepahiang. The purpose of the study was to find out the characteristics of the physical parameters that affect the potential for flooding in the upstream river and the Musi Watershed. The method used are in situ measurement and laboratory analysis. The results of research, the characteristics of the river's physical parameters after the rain, the river flow discharge is 14.50 m3/s, floating sediment discharge 1.13 kg/s, bottom sediment discharge 43 x 10-4 kg/s, and total sediment discharge 113 x 10-2 kg/s. While the condition is not raining, the river flow discharge is 5.37 m3/s, the floating sediment discharge is 0.30 kg/s, the bottom sediment discharge is 32 x 10-4 kg/s, and the total sediment discharge is 30 x 10-2 kg/s. The dominant sediment texture is sand, clay and silt with a grain size of 1.4 mm - 600 µm. The river bathymetry has a lower elevation at the confluence of the Gegasan River and Lanang River which causes the river currents to reverse, if there is an increase in rainfall it will cause flooding in the area around the river.